PENGARUH PERSEPSI PENGUSAHA DAN PENGGUNAAN PRINSIP SYARIAH TERHADAP KEBERHASILANUMKM DI KECAMATAN BANGKO - Eko Trimo Harcahyo; Sucipto; Nurlia Fusfita (Lembaga Pengembangan Kinerja Dosen, 2023)
The success of a business is the result that entrepreneurs want to achieve in running abusiness. A business can be said to be successful if it able to countinue to grow and generate incresed profiyd, this is certinlu influenced by factors such as how the perception of enterpreneurs in running a business. This research was conducted to see how the influence of the perception of enterpreneurs and the use of sharia principels on the success of UMKM in Bangko district, Merangin. The technique used in sampling is saturated sampling, which uses the entire population as a sample of 34 samples. The data used are primary data obtained directly through respondents using a questionnaire. The analysis used in this study is multiple linear regresision using SPSS. The ruslt showed that the entrepreneurs perception had an effect on the success of UMKM and the use pf sharia principles had an effect on the success of UMKM in Bangko sub district.